Brand Equity and Purchase Intention towards Passenger Cars - Bharat Rai; Dawa Sherpa (Pravaha, 2023)
The main aim of the research was to identify the factors influencing purchase intention towards passenger cars in Nepal. The study employed positivist epistemology with predefined hypotheses. Quantitative approach was utilized for the collection, presentation and analyzing the data. Primary data was collected by using a standardized questionnaire with a 6-point Likert scale. The study’s population was owners and users of passenger cars in Nepal. 385 passenger car users were sample size. Convenient sampling method was used in the study. The study employed a causal comparative research strategy. The effect of brand equity dimensions on purchase intention was identified by using regression analysis. The result of the study showed that brand association has strong significant role in the development the purchase intention and brand loyalty brand awareness, and perceived quality have also significant role but low in the development of purchase intention in Nepal. The findings of the study offer a guide to the future researchers as well as to policy maker regarding about passenger cars.